PTU-005 Circulating levels of neopterin are associated with adverse outcomes following paracetamol-induced acute liver injury. (28th May 2012) - Craig, D G; Lee, P; Pryde, A; Hayes, P C; Simpson, K J
Abstract : Introduction: Macrophage activation is implicated in the pathogenesis of multiorgan failure following paracetamol overdose (POD). Simple biomarkers of macrophage activation could aid earlier identification of high-risk POD patients. Neopterin is synthesised from macrophages and monocytes upon stimulation by interferon-γ and serum levels reflect the intensity of monocyte/macrophage activation. Methods: Consecutive patients (n=33, (15 (45.5%) male) admitted to the Royal Infirmary of Edinburgh with paracetamol-induced acute liver injury (ALT>1000 IU/l and coagulopathy) were enrolled. Serum neopterin levels were measured by ELISA (IBL International, Hamburg, Germany). Results: A total of 24/33 (72.7%) PODs developed hepatic encephalopathy (HE), and therefore acute liver failure. Neopterin levels were significantly higher in PODs (median 66.0 (IQR 25.4–96.6) nmol/l) compared with both chronic liver disease (10.8 (6.7–12.1) nmol/l, n=7, p<0.001) and healthy (11.4 (9.4–15.7) nmol/l, n=10, p<0.001) controls, but were similar to non-POD acute liver injury patients (52.5 (42.0–113.8) nmol/l, n=8, p>0.05). Admission neopterin levels were significantly higher in PODs who developed HE (HE, 72.9 (59.5–116.7) nmol/l, n=24; no HE, 20.7 (17.5–22.1) nmol/l, n=9, p<0.0001) or the systemic inflammatory response syndrome (SIRS, 79.1 (66.7–116.7) nmol/l, n=20; no SIRS, 21.6 (18.6–43.1) nmol/l, n=13, p<0.0001), and in PODs who died/required emergency liver transplantation (OLT 72.9 (68.1–119.2) nmol/l, n=14; survived 30.3 (20.7–89.1) nmol/l, n=29, p=0.006; AUROC 78.6% (95% CI 62.2% to 94.9%). An admission neopterin value of 50 nmol/l predicted death/OLT with a sensitivity of 100.0 (95% CI 76.8 to 100.0) and specificity of 63.2 (95% CI 38.4 to 83.7). Admission neopterin levels in PODs correlated with: serum creatinine (Spearman's r=0.847, p<0.0001); prothrombin time (r=0.439, p=0.011); platelet count (r=−0.463, p=0.007); IL-6 (r=0.650, p=0.0001); IL-10 (r=0.529, p=0.004); serum ferritin (r=0.467, p=0.006); and with organ failure scores (SOFA, r=0.725, p<0.0001; APACHE II, r=0.659, p<0.0001). Conclusion: Serum neopterin levels are significantly elevated following POD and are correlated with adverse outcomes. Serum neopterin may have value as an early marker of prognosis in ALF and should be assessed further with larger prospective cohorts of ALF patients. The correlation of serum neopterin with adverse outcomes provides further support for the importance of macrophage activation in the pathogenesis of multiorgan failure in ALF. Competing interests: None declared.